Dynamical Decoupling in Distance Measurements by Double Electron-Electron Resonance - Soetbeer, Janne Marie; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Spektrum, 2016)
Janne Marie Soetbeer determines the optimal dynamical decoupling (DD) scheme for efficient reduction of electron spin coherence loss in model systems for spin labelled biomolecules depending on their particular relaxation behavior. Extending the nth order DD scheme to double electron-electron resonance (DEER) experiments require the addition of multiple pump pulses for ≠ 1. Incomplete excitation of pump spin packets introduce signal artefacts which are minimized by pump pulse optimization including linear-chirp and asymmetric hyperbolic secant pulses. Prolonging the dipolar evolution time with decreased signal artefact allows to extent the measurable interspin distances in biomolecules which were otherwise not accessible due to spin echo relaxation. Contents The Spin Hamiltonian Pulsed EPR Experiments Relaxation Processes Dynamical Decoupling Model Systems Target Groups Lecturers and Students of Chemistry, especially of Physical Chemistry The Author Janne Marie Soetbeer completed her Master's Thesis at the Swiss Federal Institute of Technology in Zurich, Switzerland. After a research stay with Prof. Dr. Robert Griffin at the Massachusetts Institute of Technology in Cambridge, USA, she will be returning to Zurich to start her PhD in Prof. Dr. Gunnar Jeschke's group.
The Spin Hamiltonian -- Pulsed EPR Experiments -- Relaxation Processes -- Dynamical Decoupling -- Model Systems.
Keywords: Physical chemistry; Biophysics; Atoms; Molecules; Physical Chemistry; Biophysics; Atomic, Molecular and Chemical Physics